2017
DOI: 10.1371/journal.pntd.0005664
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of monocyte gene expression among patients with neurocysticercosis-associated epilepsy, Idiopathic Epilepsy and idiopathic headaches in India

Abstract: BackgroundNeurocysticercosis (NCC), a neglected tropical disease, inflicts substantial health and economic costs on people living in endemic areas such as India. Nevertheless, accurate diagnosis using brain imaging remains poorly accessible and too costly in endemic countries. The goal of this study was to test if blood monocyte gene expression could distinguish patients with NCC-associated epilepsy, from NCC-negative imaging lesion-free patients presenting with idiopathic epilepsy or idiopathic headaches.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Patients aged 18 to 51 years were recruited at the Department of Neurological Sciences, Christian Medical College (CMC) and Hospital, Vellore, India, as described elsewhere (Prabhakaran et al, 2017). The study was approved by the Institutional Review Boards of CMC and the University of Oklahoma HSC, USA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients aged 18 to 51 years were recruited at the Department of Neurological Sciences, Christian Medical College (CMC) and Hospital, Vellore, India, as described elsewhere (Prabhakaran et al, 2017). The study was approved by the Institutional Review Boards of CMC and the University of Oklahoma HSC, USA.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were tested for HIV, HBV and HCV only as clinically indicated. All patients were tested for antigens and antibodies for cysticercosis (Prabhakaran et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…It is also possible that differences in the pathological mechanisms governing the various models of epileptogenesis could result in the observed discrepancies in monocyte-related activity. When blood monocytes from patients suffering from neurocysticercosis (NCC), a disease related to Taenia solium (T. solium) infection and a leading cause of epilepsy in the developing world, were compared to those derived from patients with idiopathic epilepsy via microarray analysis, it was revealed that NCC-related monocytes had higher association with inflammatory/immune pathways than idiopathic epilepsy patients [145]. It has also been suggested that NCC will induce inflammatory monocyte-astrocyte crosstalk [146].…”
Section: Effect Of Monocytes Upon Status Epilepticus and Epilepsymentioning
confidence: 99%
“…In this regard, IPA analysis of differentially expressed proteins/peptides highlighted the importance of inflammation, neurological damage, blood brain barrier effects, cognition, cell death, behavior, and seizure-related pathway changes taking place in patients with SCG compared to patients with IE. Inflammatory and neurological responses have been previously documented in both NCC and SCG-related epilepsy as well as IE [1,12,50]. Finding proteins/ peptides that are known to be related to seizure phenotypes in patients with SCG and IE lends credence to the ability of the mass profiling platform and methodology described here to help decipher these pathologies.…”
Section: Discussionmentioning
confidence: 59%
“…Randomization of serum samples resulted in loss of discrimination between the groups, suggesting there exists a physiological basis for the observed patient group discriminatory results. Notably, the sensitivity test metric (true positive rate) of this LOOCV analysis exceeded that of serum EITB for SCG [13,50]. It is likely the positive results of these studies are due to the large number of different identifiers (mass peaks) applied by this approach, as opposed to more specific tests such as EITB and antigen ELISA [19,20,51].…”
Section: Discussionmentioning
confidence: 88%